Role of PhoP-PhoQ Two-Component System in Biofilm Formation of the Phytopathogen Dickeya dadantii Strain 3937 - Haque, Md Manjurul; Tsuyumu, Shinji (The Agriculturists, 2010)
To elucidate the role of PhoP-PhoQ two-component system in biofilm formation by the phytopathogen Dickeya dadantii (formerly Erwinia chrysanthemi) strain 3937, we used marker-exchanged mutants deficient in both phoP and phoQ. A biofilm-inducing medium, salt-optimized broth plus glycerol (SOBG) which contains salt-optimized broth (SOB) plus 2% of glycerol, supported biofilm formation by D. dadantii strain 3937 to a greater extent than either M63 glycerol minimal medium or yeast extract peptone (YP) medium or Luria-Bertani (LB) medium. In addition, magnesium greatly induced biofilm formation. It was found that both the phoP and phoQ mutants exhibited enhanced ability to form a biofilm on the surface of the glass test tube as compared to the wild-type strain in SOBG medium containing high concentration of magnesium. In addition, under high magnesium condition, both the mutants produced elevated level of exopolysaccharide. Accordingly, genes responsible for exopolysaccharide production (weaP, wza and wzc) were derepressed in the mutants. These results suggest that the PhoP-PhoQ two-component system may regulate formation of biofilm, at least in part, by transcriptional control of genes responsible for exopolysaccharide biosynthesis of D. dadantii strain 3937. Since biofilm-associated bacteria showed more tolerance to acidic pH and high osmotic stress, it is apparent that the formation of biofilm may be an important factor for the survival of D. dadantii strain 3937 in unfavorable environment.